Cognition and Ideology in the Irony of the Batak Toba Language - Siagian, Beslina Afriani; Mulyadi, Mulyadi (Bina Nusantara University, 2023)
The research discussed the irony of the Batak Toba language that was studied in two domains at once, namely the realization of the process of cognition and the realization of social praxis. The process of cognition was analyzed using a conceptual metaphorical approach, while social praxis used a critical discourse analysis approach of Fairclough's model. The research involved the qualitative research. The data obtained from various sources, such as eight song lyrics, nine folk tales, two sermons, one traditional procession, and two oral conversations. Data collection was done by sorting out which expressions were classified as irony, determining metaphors, mapping the source and target domains, then identifying cognitive processes and social praxis. It is found that irony in the Batak Toba language realizes the ability of cognition, which can be seen from the use of metaphors of animals, plants, body parts, and even inanimate objects in conceptualizing character, identity, attitudes, behavior, and human existence. Irony in the Batak Toba language also realizes social praxis. This is because irony shows a connection with the surrounding nature, describes the reality of social value identity, shows euphemism expressions to avoid social conflict, and describes ideology in maintaining good horizontal relations. Thus, it can be concluded that the irony of the Batak Toba language realizes the ability of cognition and ideology of the Batak Toba people, which can reflect the local wisdom of the community itself.